Putri Renjani Manisan Product Standardization: The Efforts to Increase Product Sales in Pandemic Situations - Nurmala Berutu; Hodriani Hodriani; Dwi Budiwiwaramulja (Randwick International of Social Science Journal, 2021)
Recently, Indonesia experienced a major disaster caused by Covid-19 which was also experienced by other countries such as China. This had a huge impact so as to shake the stability of the country. Attacking public health, especially the economy. The Covid-19 pandemic in Indonesia has occurred since March 2020 until now. This also has an impact on the income of creative businesses or home industries. This research will specifically examine the role of Putri Ranjani Manisan product standardization in the Business Group for Increasing Prosperous Family Income (Usaha Peningkatan Pendapatan Keluarga Sejahtera/ UPPKS) Kasih Ibu Kampung KB, Limau Sundai Binjai Village and product commercialization in an effort to increase income during this pandemic. The research method used to examine this research is to use qualitative method with an experimental approach to the existence of the creative industry "Putri Ranjani Manisan" in the Business Group for Increasing Prosperous Family Income (UPPKS) Kasih Ibu Kampung KB Limau Sundai Binjai Village. The research results show that the role of standardization is very helpful in increasing the quantity of product sales during this pandemic. The role of standardization also supports the quality of product quality, from taste, hygiene, packaging, and halal certificates to products. During the pandemic, consumers prioritize trust in clean and hygienic products and can be trusted through MUI halal certificate. In addition, home industrial products must also have good and clean management in the process of managing products, especially food products. Therefore, local governments must play a role in providing support for creative household businesses so that they are more able to compete in the global market and support the regional economy.